PATRIARCHY IN SYLVIA PLATHâ€™S â€œDADDYâ€ - Diakanova, Wendy Sambada; Yustisiana, Rr. Arielia (Humaniora Scientia, 2019)
The research aimed to discuss patriarchy in Sylvia Plathâ€™s â€œDaddyâ€. There were two objectives of the study. The first was to portray the patriarchy in Sylvia Plathâ€™s â€œDaddyâ€. The second was to analyze the symbols of patriarchy in Sylvia Plathâ€™s â€œDaddyâ€. This research applied four theories. They were ideology, patriarchy, oppressor, and symbol. The ideological and structural approaches were used in this research. The result of the research showed the portrayal of patriarchy in fatherâ€™s and husbandâ€™s figure. From the fatherâ€™s figure we can understand that a parent who is the dominant ruler of his daughterâ€™s life will leave such a painful loss after his death comes so that his daughter loses his guidance in life. While, from the husbandâ€™s figure we can learn that patriarchy also happens in a marriage. Furthermore, the symbols dealing with patriarchy is revealed in the description of confinement life, fear, regretful loss, and unhappy marriage. Keywords: ideology, patriarchy, oppressor, symbol